Bet against yourself: integrating insurance and entrepreneurship. Issue 6 (25th December 2021) - Eabrasu, Marian
Abstract: This paper revisits and fine-tunes a spin-off from Knight's (1921, Risk, Uncertainty and Profit) influential distinction between risk ('probability of unknown events') and uncertainty ('unquantifiable randomness'): the contrast between actuarial institutions and entrepreneurship. It contends that this opposition is not exclusive and argues that the act of insurance does not automatically reduce entrepreneurial profits. To maintain this claim, the paper emphasizes hedging and, more specifically, draws on an innovative actuarial scheme – parametric (or index-based) insurance – which, unlike indemnity-based insurance, does not rely on a damage assessment but indemnifies the policyholder according to the variation of an index. This argument sheds new light on the function habitually assigned to actuarial institutions, amends the theory of entrepreneurial profits, and integrates hedging within entrepreneurial judgment.